KOLABORASI GURU PENDIDIKAN AGAMA ISLAM DAN BIMBINGAN KONSELING DALAM MEMPERKUAT KESEHATAN MENTAL DAN ANTISIPASI BULLY PADA PESERTA DIDIK DI MTSN 3 PADANG PARIAMAN - YARMAINI YARMAINI (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
Mental health and bullying prevention in schools require collaborative approaches, yet the synergy between Islamic Religious Education (PAI) teachers and Guidance and Counseling (BK) teachers remains understudied. At MTsN 3 Padang Pariaman, the lack of integration between religious and psychological approaches has hindered optimal outcomes. This research addresses this gap by exploring a collaborative model grounded in Islamic values and modern psychology. This study aims to: 1) analyze the synergistic roles of PAI and BK teachers in strengthening students’ mental health, 2) develop an Islamic value-based collaboration model for bullying prevention, and 3) provide policy recommendations for schools. A qualitative case study was employed, with data collected through interviews and observations. Thematic analysis followed Miles, Huberman, and Saldana’s interactive model, focusing on condensation, display, and conclusion drawing. The collaboration significantly reduced bullying cases and enhanced mental resilience through integrated programs. Key findings include: 1) the effectiveness of combining tazkiyatun nafs (spiritual purification) with cognitive-behavioral techniques, and 2) the importance of holistic school policies. The study contributes to Islamic counseling theory and offers practical frameworks for Islamic schools.